International Review of the Red Cross : Human debate : law, policy, action; humantarian rights - Pfanner, Toni (Cambridge : Cambridge University Press)
Established in 1869, the International Review of the Red Cross is a quarterly published by the International Committee of the Red Cross (ICRC) and Cambridge University Press. It is a forum for debate on international humanitarian law and humanitarian action and policy, during armed conflict and other situations of violence. It is dedicated to governments, international governmental and non-governmental organisations, universities, the media and all those interested in humanitarian issues at large. On-line copies of the Review dating back to 1995 are available.
Keywords: International Committee of the Red Cross; Humanitarian law